PROFILE OF NONFERMENTING GRAM NEGATIVE BACILLI IN A TERTIARY CARE HOSPITAL LABORATORY - Dr Lopamudra; Dr Aruna Rani Behera; Dr Swetalina Jena; Dr Dibya Prasana Mohanty (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Non-Fermentative or Non Fermenting Gram Negative Bacilli (NFGNB) are widely distributed in nature as saprophytes, found in soil, water, sewage or as commensals on human skin or in the human gut and some in hospital environment. These organisms are commonly isolated from patients with serious underlying diseases such as patients with prolonged antibiotic therapy, endotracheal intubation, catheterization, burn patients and in extremes of age like neonates, children and geriatrics age group. They are responsible for septicemia, meningitis, brain abscess, endocarditis, pneumonia, urinary tract infection and surgical site infections. Materials and Methods: This a prospective study, conducted in the Department of Microbiology, VSS Medical College & Hospital, Burla over a period of two years from October 2014 to September 2016. A total of 9204 non repetitive clinical specimens like sputum, throat swabs, endotracheal tube secretions, pus, urine, blood, and body fluids were collected using strict aseptic precautions from various clinical departments and immediately processed. Observation & Results: In this study 9204 clinical samples were processed in Microbiology Laboratory, out of which 3955 specimens showed growth; 571 of these positive cases showed mixed cultures of two organisms. Hence total number of isolates summed upto 4526, including 1350 isolates of gram-negative bacilli. Out of these, 505 cases are found to be nonfermenters. Pseudomonas aeruginosa is the most common isolate accounting for 349 (69.30%) followed by Acinetobacter baumanii 84(16.63%) and next to it is Pseudomonas fluorescens 42(7.92%). The maximum number of cases are from Surgery ward accounting for 26.53% followed by Medicine ward 20.39% and 17.82% from Obstetrics and Gynaecology ward. The most effective drugs against Pseudomonas aeruginosa isolates showed sensitivity to Meropenem (78%) followed by Imipenem (73.56%) and Amikacin (51.23%). A.baumannii isolates showed highest sensitivity to meropenem (76%) followed by imipenem(74%) and chloramphenicol(62%)., S.maltophila showed 100% resistance to ceftazidime and cefotaxime, but 100% sensitive to amikacin, imipenem, meropenem, aztreonam, and ciprofloxacin. Conclusion: Most of the NFGNB are resistant to commonly used antibiotics, hence antibiogram should be followed before successfully treating these cases. Above all, the Hospital Infection Control Committee should be active enough to avoid infections due to NFGNB as well as other organisms and the Hospital Antibiotic Policy should be followed strictly.